1985
DOI: 10.2337/diab.34.7.671
|View full text |Cite
|
Sign up to set email alerts
|

Elevated In Vivo Insulin Clearance in Pima Indians with Non-insulin-dependent Diabetes Mellitus

Abstract: In vivo insulin clearance in 10 subjects with non-insulin-dependent diabetes mellitus (NIDDM) has been compared with clearance in eight equally obese nondiabetic control subjects by two different methods. The first approach consisted of determining the metabolic clearance rates of exogenously infused insulin (MCRI) during hyperinsulinemic (100 mU/m2/min) glucose clamp studies. The results indicated that mean (+/- SEM) MCRI was 1.4-fold greater in the diabetic subjects (436 +/- 22 ml/m2/min) than in the control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…First, we did not perform a pancreatic clamp to completely suppress endogenous insulin secretion throughout the experiment (basal period and clamp). To take this fact into consideration, we adjusted the calculation of MCRI according to the suppression of C-peptide level using a previously published method 30, 31 . Second, we recruited only Japanese in this study, thus our results may not be applicable to other ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…First, we did not perform a pancreatic clamp to completely suppress endogenous insulin secretion throughout the experiment (basal period and clamp). To take this fact into consideration, we adjusted the calculation of MCRI according to the suppression of C-peptide level using a previously published method 30, 31 . Second, we recruited only Japanese in this study, thus our results may not be applicable to other ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…Vasquez et al have reported that obese Pima Indians with type I1 diabetes have increased clearance of insulin relative to obese non-diabetic Indians [27], thus partially explaining the low post glucose challenge insulin concentrations in the former. It would be of considerable interest to follow the non-diabetic Pima Indians to determine whether the clearance of insulin changes after the onset of the diabetic state or, alternatively, whether clearance of insulin (as well as insulin sensitivity [5]) predicts the onset of type I1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the kinetics of insulin in diabetes as compared to the normal state have given conflicting results: the insulin disappearance rate from the blood stream has been reported to be increased (Navalesi et al 1983;Vasquez et a/. 1985), unchanged (Silvers et al 1969;Brskov & Christensen 1969;Genuth 1972;Navalesi et al 1978;McGuire et al 1979;Del Prato et al 1983) or decreased (Stimmler et al 1972;Frost et Gray et a/.…”
mentioning
confidence: 99%